2022
DOI: 10.1111/rsp3.12519
|View full text |Cite
|
Sign up to set email alerts
|

What drives the changes in public transport use in the context of the COVID‐19 pandemic? Highlights from Lyon metropolitan area

Abstract: This article focuses on the decline in the use of public transport in the context of the coronavirus disease 2019 (COVID‐19) crisis in the Lyon metropolitan area, France. Using data from a web‐based survey, supplemented by traffic counts and a qualitative survey, we explain this decline by the decrease in out‐of‐home activities such as work and the concomitant increase in teleworking, as well as by modal transfers. We test these explanations by multiple regression models that include socio‐demographic, residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A transition to teleworking caused a decrease in public transport. Active transport recorded an increase due to the transfer of passengers from public transport [63]. Travel mode choice was reflected in another study.…”
Section: Discussionmentioning
confidence: 85%
“…A transition to teleworking caused a decrease in public transport. Active transport recorded an increase due to the transfer of passengers from public transport [63]. Travel mode choice was reflected in another study.…”
Section: Discussionmentioning
confidence: 85%
“…As evidence of spatial segregation has already been shown in terms of socioeconomic profiles in Lyon (Bouzouina et al, 2021), further analysis should investigate the link between spatially varying impact, land use (space function), and sociodemographic data. El Zein et al (2022) demonstrated the correlation between the drop in PT use in Lyon and the possibility to work from home or choosing an alternative mode in Lyon.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of COVID‐19 on travel behavior have been abundantly studied in different spatial contexts, at different levels, and using different data sources and methodologies (Bouzouina et al, 2022). PT data are largely used at aggregated levels, such as regional (Jenelius & Cebecauer, 2020; Manout et al, 2023), or municipal (Aloi et al, 2020; El Zein et al, 2022; Gramsch et al, 2022) levels. These levels are often suitable for sociodemographic analysis, which combines activity or demographic data available for the same level of aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic, several studies have been undertaken to assess its impacts on PT use at different spatial levels (Al Zein et al 2022;Bouzouina et al 2022;Eisenmann et al 2021;Jenelius et al 2020;Jiang et al 2022;Melo 2022;Rasca et al 2021;Séjournet et al 2022;Wielechowski et al 2020). These studies report various findings: decline in PT use in favor of the car, the impact of policy stringency on PT, fear of contamination in PT, and the wide adoption of remote activities, particularly during the first months of the pandemic (Gkiotsalitis et al 2021).…”
Section: Introductionmentioning
confidence: 99%